Assessment of the Adequacy of Drug Choice in Patients with Acute Myocardial Infarction According to the PROFILE-IM Registry - S. Yu. Martsevich; N. P. Kutishenko; E. P. Kalaydzhyan; D. P. Sichinava; V. A. Evdakov (Столичная издательская компания, 2019)
Background. The prognosis for patients after acute myocardial infarction (AMI) can be improved by prescribing beta-blockers (BB), angiotensin converting enzyme inhibitors (ACEI) and statins. This is reflected in the current clinical guidelines, in which these drugs are considered mandatory for almost all patients after AMI. However, not all representatives of the same drug class have the same evidence base in relation to the impact on the outcomes of AMI, in addition, not all BB and ACEI, according to the official instructions have the indication "recent AMI".Aim. To assess the adequacy of the choice of BB, ACEI and angiotensin receptor antagonists (ARA), prescribed after recent AMI, using the materials of the prospective registry PROFILE-IM.Material and methods. 1 60 patients after AMI referred to outpatient clinic from March 01,2014 to June 30, 201 5 were included into the registry. The therapy prescribed to patients at discharge from the hospital and at the first visit to the outpatient clinic were evaluated, special attention was paid to three classes of drugs: BB, ACEI/ARA.Results. The majority of patients were recommended ACEI/ARA (88.1%) and BB (98.8%) at discharge from hospital. Not prescribing of these groups of drugs in about half of the cases had a reasonable cause, for ACEI/ARA in 13 patients (8.1%) the cause could not be clarified. When choosing a BB in most cases (both in hospital and in the outpatient clinic) preference was given to bisprolol (61% and 67%, respectively), which has no evidence of prognosis improvement for patients after AMI, the second place took metoprolol, its prescription was two times less than bisprolol. When choosing ACEI, priority was given to perindopril, with which no one randomized clinical trial was carried out in patients after AMI (38% of prescriptions in the hospital and 41% - in the outpatient clinic). Enalapril took the second place (20% and 22%, respectively), the remaining ACEI were prescribed much less frequently, ARA were also prescribed rarely (5%).Conclusion. After AMI the majority of patients were prescribed BB, ACEI/ARA, which in accordance with current clinical guidelines are necessary to improve long-term outcomes. However, the choice of a specific drug within the drug class not always consistent with evidence-based medicine, current clinical guidelines and the official instructions for the medical use. In this regard, patients after AMI do not receive all the benefits of drug therapy to improve long-term outcomes.